2022
DOI: 10.3390/sym14112252
|View full text |Cite
|
Sign up to set email alerts
|

An Insight of the Theoretical Physics of Ru-Alloyed Iron Pyrite Studied for Energy Generation

Abstract: Pyrite FeS2 has become the focus of many researchers in thin-film photovoltaics because it has some possibilities in photovoltaics. In this manuscript, we present an experimental and a theoretical study of the electronic structure of pyrite FeS2 alloyed with a small concentration of 1.19% of ruthenium (Fe0.9881Ru0.0119S2) by using the Linear Muffin-Tin Orbital Method in the Atomic-Sphere approximation (LMTO-ASA) calculations and the density of states. We observed that the bandgap of FeS2 increases from 0.90508… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A remarkable change of band gap calculated depend constant lattice change, band gap value decreases with increases of constant lattice. We conclude that the use of Ru as an alloying for iron pyrite is the perfect way as previewed by many researchers [ [66] , [67] , [68] ].…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…A remarkable change of band gap calculated depend constant lattice change, band gap value decreases with increases of constant lattice. We conclude that the use of Ru as an alloying for iron pyrite is the perfect way as previewed by many researchers [ [66] , [67] , [68] ].…”
Section: Resultsmentioning
confidence: 53%
“…We utilized spray pyrolysis technical for formation of our samples, which this method is well described in Refs. [ 52 , 53 ]. In our strategy, we use of a mixture resulted from the dissolution of 8.5 g of and within a molar ratio as : = x:1 − x (x = 0.3966, 0.1586, 0.0496, 0.0347, 0.0106 and 0.00) through 7 min substrates for temperature of heated at 400 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, N. Alonso –Vante et al studied Cu-alloyed FeS2 structure phase, which is significantly affected by the deficiency of sulfur, their obtained films we can see that the conductivity p-type and the band gaps values were: 1.062–1.156 eV [ 51 ]. Nofal et al showed that the bandgap of FeS2 increases from 0.90508 to 1.21586 eV when they replace ∼1.19% of the Fe atoms with ruthenium atoms (x = 0.0119 concentration of Ru) [ 52 ]. Sun et al claimed that the band gap of FeS2 pyrite (0.95 eV) increases when alloys with Os to (1.2eV) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%